Does age among landscape architect's affects the perception on landscapes of tropical recreational forests? - Hussein, Mohd Kher (GRDS Publishing, 2019)
Perception of our environment helps us to understand and react to our environment. But, in the perception process, a number of factors seem to influence perception for a landscape such as age. Therefore, this study aimed to investigate whether the age factors among landscape architect’s affects for landscape perception of tropical recreational forest in Malaysia. A study was conducted in Ampang Recreational Forest, Selangor as a case study. This study using a questionnaire with photographs surrogates to gather data from 119 expert landscape architects. Results have shown that there is no statistical significant effect of age among professional landscape architects in perception for tropical recreational forest landscapes in this study. Thus, this result portrays that age of the respondent in the same group does not statistically affect landscape perception.